Value-based modeling and simulation for sustainable ICT4D - Omotola, Akindoyo Oluwatosinloba; Waishiang, Cheah; Khairuddin, Muhammad Asyraf bin; Jalil, Nurfauza binti; Phang, Eaqerzilla (Society of Visual Informatics, 2023)
ICT4D is an acronym for information and communication technologies for development. This acronym represents the many initiatives that are now being carried out in underdeveloped countries all around the globe. These technology-oriented initiatives aim to promote the growth and prosperity of the regions they serve. People from the local community often volunteer their time to serve as program managers when NGOs or governments give funding. The term